2016
DOI: 10.2196/jmir.5654
|View full text |Cite
|
Sign up to set email alerts
|

The Pros and Cons of Getting Engaged in an Online Social Community Embedded Within Digital Cognitive Behavioral Therapy for Insomnia: Survey Among Users

Abstract: BackgroundSleepio is a proven digital sleep improvement program based on cognitive behavioral therapy techniques. Users have the option to join an online community that includes weekly expert discussions, peer-to-peer discussion forums, and personal message walls.ObjectiveThe aim of this study was to conduct an online survey to (1) explore the reasons for deciding to engage with the Sleepio online community, (2) explore the potential benefits arising from engagement with the online community, and (3) identify … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
32
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(39 citation statements)
references
References 36 publications
6
32
0
1
Order By: Relevance
“…Reasons for low usage were similar to those found in other evaluations of online forums, including doubts about the trustworthiness of the information provided, perceived negativity of the forum posts, concerns regarding internet safety, and negative views of the forum platform [21,30]. Unique to this population, some users were concerned that participation in the forum would make their tinnitus worse by focusing on it or highlighting people's negative tinnitus experiences.…”
Section: Key Contrasting Findings Between Study 1 Andsupporting
confidence: 59%
“…Reasons for low usage were similar to those found in other evaluations of online forums, including doubts about the trustworthiness of the information provided, perceived negativity of the forum posts, concerns regarding internet safety, and negative views of the forum platform [21,30]. Unique to this population, some users were concerned that participation in the forum would make their tinnitus worse by focusing on it or highlighting people's negative tinnitus experiences.…”
Section: Key Contrasting Findings Between Study 1 Andsupporting
confidence: 59%
“…Several MAs have been developed to monitor sleep. For example, the CBT-I Coach, 4 Sleepio, 7 Win-Win aSleep, 8 and SleepRate 9 applications were developed to track sleep or facilitate CBT-I. Previous pilot studies found that CBT-I Coach improved sleep in 4 patients with cannabisuse disorder 10 ; when used as an adjunct to CBT-I, the MA improved adherence and sleep outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…In line with the literature [6,18,26], the success or failure of digital services such as a mobile phone app in encouraging a healthier lifestyle is highly dependent on the app's efficacy in achieving behavioral change. Based on research exploring game-based health interventions [13,15], as well as theories and practice of designing for change [20], our findings suggest that in the context of smoking cessation, psychological empowerment through the gamified design of a mHealth app significantly predicts users' ability to quit smoking successfully.…”
Section: Extending Extant Knowledgementioning
confidence: 67%
“…Contrary to our common intuition, the inspiring element of the app was negatively associated with both the probability of successfully quitting smoking and the reduction in cigarettes smoked per day. While inspiration can motivate and encourage individuals to keep going [16,26,27], it can also reduce individual's sense of selfresponsibility at times. As prior research notes [28,29], inspiration is not the same as positive affect; people who enter an inspired state (by thinking of a moment when they were inspired) reported lower levels of volitional control, controllability, and selfresponsibility for their inspiration.…”
Section: Extending Extant Knowledgementioning
confidence: 99%